Monitoring of stress variation of strands in prestressed concrete by second harmonic generation measurements based on piezoelectric sensors. (19th November 2021) - Chen, Jun; Wan, Xiaohan; Guo, Quanquan
Abstract: The stress loss of prestressed concrete may cause the ultimate failure of structures and the monitoring of stress variation of prestressed structures is therefore important to ensure the service safety. This paper developed a nondestructive evaluation method of nonlinear ultrasonic second harmonic generation (SHG) based on piezoelectric (PZT) sensors and applied for the distinction of different stress level of post-tensioned steel strands in concrete. The nonlinear ultrasonic behavior of both free strand and embedded strand having different length is studied with the developed SHG technique and a defined nonlinear parameter is introduced in SHG experiments to correlate with the tension stress in the strand. It is found that the nonlinear parameter has a negative correlation with the increasing stress of strand in both free and embedded case, indicating the nonlinear ultrasonic behavior is getting weak corresponding to the increasing contact force among strand wires. In addition, the decreasing ratio of nonlinear parameter is very close to each other regardless of the length of steel strand, indicating the possibility of replacing the large-scale on-site testing with scaled down samples in laboratory. The experimental results of this research demonstrate that the SHG technique based on PZT sensors could be useful for the stress monitoring of prestressed reinforced concrete with consideration of the relatively high sensitivity of nonlinear parameter to the variation of contact force of strand wires.